2016
DOI: 10.1186/s12885-016-2485-9
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant irinotecan, cisplatin, and concurrent radiation therapy with celecoxib for patients with locally advanced esophageal cancer

Abstract: BackgroundPatients with locally advanced esophageal cancer who are treated with trimodality therapy have a high recurrence rate. Preclinical evidence suggests that inhibition of cyclooxygenase 2 (COX2) increases the effectiveness of chemoradiation, and observational studies in humans suggest that COX-2 inhibition may reduce esophageal cancer risk. This trial tested the safety and efficacy of combining a COX2 inhibitor, celecoxib, with neoadjuvant irinotecan/cisplatin chemoradiation.MethodsThis single arm phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 43 publications
3
7
0
Order By: Relevance
“…They found that the addition of celecoxib to neoadjuvant cisplatin–irinotecan chemoradiation was tolerable; the OS appeared comparable to prior studies using neoadjuvant cisplatin–irinotecan chemoradiation alone. 44 The further mechanism of anticancer effects of COX-2 inhibitors should be elucidated, and results from large randomized clinical trials are needed to provide useful information in further establishing the efficacy of COX-2 inhibitors in adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the addition of celecoxib to neoadjuvant cisplatin–irinotecan chemoradiation was tolerable; the OS appeared comparable to prior studies using neoadjuvant cisplatin–irinotecan chemoradiation alone. 44 The further mechanism of anticancer effects of COX-2 inhibitors should be elucidated, and results from large randomized clinical trials are needed to provide useful information in further establishing the efficacy of COX-2 inhibitors in adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective phase II trial of neoadjuvant chemotherapy followed by surgical resection in a contemporary group of 40 patients with esophageal cancer (85% with adenocarcinoma), Cleary et al reported that six patients (15%) developed brain metastasis at a median of 13.9 months after surgery [15]. In ve of the six patients, adenocarcinoma was the primary histology and brain was the rst site of metastasis in four of 40 patients (10%).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, adenocarcinoma was the primary histology in all cases of brain metastasis. Subsequently, a prospective trial of neoadjuvant chemotherapy followed by surgical resection in a contemporary cohort of patients with esophageal carcinoma reported a similar incidence of brain metastasis of 15%, also noting a predominance of adenocarcinoma histology [15].…”
Section: Introductionmentioning
confidence: 94%
“…The current study first elucidated the antitumor effect of the combination of COX-2 inhibitor and brachytherapy in patients with prostate cancer. Although no report has evaluated the antitumor effect of the combination of COX-2 inhibitor and radiation therapy in prostate cancer, the efficacy of combination therapy was evaluated in patients with rectal cancer, 17 non-small-cell lung cancer, 18,19 glioblastoma, 20 nasopharyngeal carcinoma, 21 esophageal cancer 22 and pancreatic cancer. 23 Decucquoy et al reported that patients with rectal cancer treated with radiation (45 Gy; 1.8 Gy/fraction) and celecoxib (800 mg/day; n = 18) as neoadjuvant therapy were more likely to have a better response (61%) than those treated with radiation and placebo (n = 17; 35%).…”
Section: Discussionmentioning
confidence: 99%